Spin–momentum locking induced non-local voltage in topological insulator nanowire. Issue 45 (18th November 2020) - Chen, Jen-Ru; Tse, Pok Lam; Krivorotov, Ilya N.; Lu, Jia G.
Abstract : Unique spin–momentum locking in topological surface states of Sb2 Te3 nanowires exhibits an unusual symmetry in non-local voltage signal. Abstract : The momentum and spin of charge carriers in the topological insulators are constrained to be perpendicular to each other due to the strong spin–orbit coupling. We have investigated this unique spin–momentum locking property in Sb2 Te3 topological insulator nanowires by injecting spin-polarized electrons through magnetic tunnel junction electrodes. Non-local voltage measurements exhibit an asymmetry with respect to the magnetic field applied perpendicular to the nanowire channel, which is remarkably different from that of a non-local measurement in a channel that lacks spin–momentum locking. In stark contrast to conventional non-local spin valves, simultaneous reversal of magnetic moments of all magnetic contacts to the Sb2 Te3 nanowire alters the non-local voltage. This unusual asymmetry is a clear signature of the spin–momentum locking in the Sb2 Te3 nanowire surface states.